2022
DOI: 10.1002/sd.2394
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among sustainable development goal 15 (life on land) and other sustainable development goals: Knowledge for identifying global conservation actions

Abstract: Sustainable development goals (SDGs) and their targets were designed to be interlinked. Understanding the interactions among SDGs is crucial to prioritize and implement actions that maximize synergies between SDGs while minimizing trade-offs, which can accelerate the overall progress toward all SDGs. Since the 2021 United Nations Climate Change Conference reaffirmed the importance of SDG 15 (life on land), defining conservation actions for implementing SDG 15 in the context of considering the interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(86 reference statements)
2
5
0
Order By: Relevance
“…Trade‐offs are not inherent to targets or goals themselves, but rather stem from inadequate governance and lack of coordination among different sectors (Breuer et al, 2019). We found that SDG 15 is a buffer of trade‐offs at the systemic level, in line with other global studies (Huan & Zhu, 2022; Pham‐Truffert et al, 2020), meaning that addressing challenges to SDG 15 will largely depend on actors from other sectors considering and addressing trade‐offs between SDG 15 and other goals. Therefore, policy‐makers responsible for SDG 15 need to work together with relevant ministries and departments across all levels of the government, especially including Nepal's Ministry of Energy, Water Resources and Irrigation, and Ministry of Physical Infrastructure and Transportation in this case.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Trade‐offs are not inherent to targets or goals themselves, but rather stem from inadequate governance and lack of coordination among different sectors (Breuer et al, 2019). We found that SDG 15 is a buffer of trade‐offs at the systemic level, in line with other global studies (Huan & Zhu, 2022; Pham‐Truffert et al, 2020), meaning that addressing challenges to SDG 15 will largely depend on actors from other sectors considering and addressing trade‐offs between SDG 15 and other goals. Therefore, policy‐makers responsible for SDG 15 need to work together with relevant ministries and departments across all levels of the government, especially including Nepal's Ministry of Energy, Water Resources and Irrigation, and Ministry of Physical Infrastructure and Transportation in this case.…”
Section: Discussionsupporting
confidence: 91%
“…Trade-offs are not inherent to targets or goals themselves, but rather stem from inadequate governance and lack of coordination among different sectors (Breuer et al, 2019). We found that SDG 15 is a buffer of trade-offs at the systemic level, in line with other global studies (Huan & Zhu, 2022;Pham-Truffert et al, 2020) Even with collaboration, a win-win situation is not always possible, and difficult compromises are inevitable (Bowen et al, 2017). As Nepal is a low-income country, its government prioritizes socio-economic development with various nation-wide infrastructure projects, while subsistence requirements will always be a priority for local communities (Sharma et al, 2018), despite generally high awareness and positive attitudes toward biodiversity and conservation (Dhungana et al, 2022;Hanson et al, 2019).…”
Section: Opportunities For Addressing Conservation and Development Tr...supporting
confidence: 87%
See 1 more Smart Citation
“…References: Alcamo (2019); Avrampou et al (2019); Booth (2019); Camilleri (2019); Cramer et al (2018); Dawes (2020); Galford et al (2020); Gracia‐de‐Rentería et al (2022); Honegger et al (2021); Huan and Zhu (2023); Kempf and Dutta (2021); Lang et al (2022); Lee (2020); Lyytimäki et al (2020); Meschede and Henkel (2019); Nayak and Jespersen (2022); Nepal and Paija (2019); Puchol‐Salort et al (2021); Royston et al (2020); Schroeder et al (2019); Singh (2022); Stead (2018); Tan et al (2021); Tselios and Tompkins (2019); Weststrate et al (2019); Yao et al (2021); Zhou et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conservation effectiveness is a pressing global issue (Bennett, 2016). Aichi Target 11 of the Convention on Biological Diversity requires protected area (PA) networks to be effectively and equitably managed (Watson et al, 2014), directly related to achieving Sustainable Development Goal 15 (Huan & Zhu, 2023). However, numerous conservation initiatives have yet to guarantee successful protection (Appleton et al, 2022; Edgar et al, 2014) or benefit humans (Bennett & Dearden, 2014; West et al, 2006); only one‐third of current terrestrial PA is assessed as effectively managed (UNEP‐WCMC & IUCN, 2021).…”
Section: Introductionmentioning
confidence: 99%